2022
DOI: 10.2147/jbm.s358993
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Epidemiology, Treatment Outcome and Mortality Rate of Newly Diagnosed Immune Thrombocytopenia in Adult Multicentre Study in Malaysia

Abstract: Background Immune thrombocytopenia (ITP) is well characterized in Western, European and other Asia-Pacific countries. Nevertheless, the clinical epidemiology, treatment pattern and disease outcome of ITP in Malaysia are still limited and not well known. Objective This study aimed to describe the clinical epidemiology, treatment outcome and mortality of ITP patients in haematology tertiary multicentre in Malaysia. Methods Clinical and laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 70 publications
(63 reference statements)
4
9
2
Order By: Relevance
“…Most epidemiologic data suggest that women are more commonly affected by ITP during their childbearing age and that the prevalence after menopause is similar to that of men [6][7][8]43,44 . In this study, 75.5% of the study participants were female, which is consistent with other studies from the United States of America (76%) 45 , Turkey (71.3%) 46 , and Malaysia (71.8%) 36 . In our study, the proportion of females was higher than that in studies conducted in the United Kingdom (56.9%) 8 , Germany (57%) 47 , China (63.6%) 48 , and in the ITP World Impact Survey data (65%) 17 but lower than that in studies conducted in Mexico (81.8%) 49 and Egypt (84%) 50 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Most epidemiologic data suggest that women are more commonly affected by ITP during their childbearing age and that the prevalence after menopause is similar to that of men [6][7][8]43,44 . In this study, 75.5% of the study participants were female, which is consistent with other studies from the United States of America (76%) 45 , Turkey (71.3%) 46 , and Malaysia (71.8%) 36 . In our study, the proportion of females was higher than that in studies conducted in the United Kingdom (56.9%) 8 , Germany (57%) 47 , China (63.6%) 48 , and in the ITP World Impact Survey data (65%) 17 but lower than that in studies conducted in Mexico (81.8%) 49 and Egypt (84%) 50 .…”
Section: Discussionsupporting
confidence: 92%
“…Treatment outcome tools. After an extensive review of the literature [36][37][38][39] and with the help of experts, structured questionnaires were designed to evaluate the treatment outcomes of ITP patients.…”
Section: Data Collection Instrumentsmentioning
confidence: 99%
“…Our study confirms that the prevalence of Malay ITP patients is the highest compared to other ethnic groups (Chinese and Indian), as reported by previous local studies in Perak and Selangor [ 9 , 14 ]. About 63% of the total population in Peninsular Malaysia is constituted by Malays [ 18 ], thus establishing their dominance in the research.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, our study noted a significantly higher ITP incidence rate among females compared to males, which is comparable with previous studies from the United Kingdom (58.22/100,000 versus 40.66/100,000 person-years) and France (3.03/100,000 versus 2.77/100,000 person-years) [ 2 , 20 ]. Additionally, local research also observed higher ITP rates among female young adults (<65 years old) [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation